1991
DOI: 10.1093/bja/67.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Finapres and Direct Arterial Pressure Monitoring During Profound Hypotensive Anaesthesia

Abstract: The Finapres was compared with direct intraarterial pressure monitoring in 10 patients undergoing local resection of choroidal melanoma, an operation that requires a period of profound hypotension. Good agreement was recorded for systolic arterial pressure and heart rate over a range of pressures. However, agreement of mean and diastolic pressures was poor, with the Finapres tending to overestimate these values. In cases requiring profound hypotension, direct arterial pressure monitoring remains the method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 4 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…The Finapres method, of which Nexfin is an evolution, has been utilized in a variety of settings, such as drug-induced hypotension during hypotensive anaesthetic techniques, 1012 tilt testing, 1316 Valsalva manoeuvre, 17,18 and exercise stress tests. 19,20 However, it has not yet been used during interventional electrophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…The Finapres method, of which Nexfin is an evolution, has been utilized in a variety of settings, such as drug-induced hypotension during hypotensive anaesthetic techniques, 1012 tilt testing, 1316 Valsalva manoeuvre, 17,18 and exercise stress tests. 19,20 However, it has not yet been used during interventional electrophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Our experimental setting did not allow evaluation of the accuracy of the FINA method in these critical situations. However, previous studies in adults have reported the reliability of this method during profound hypotensive anaesthesia (26) and during exercise-or drug-induced hypertensive states (4). Further investigations may be required in children.…”
Section: Systolic Gradientmentioning
confidence: 99%
“…To date, only the Finapres monitor has seen extensive clinical assessments. [5][6][7][8][9] The N-CAT N-500 is a newly developed, noninvasive, to evaluate the accuracy and reliability of N-CAT N-500 monitor. This study found a lower systolic TBP (bias -1.71 + 4.6), and a higher diastolic TBP (bias 0.99 + 4.56) but no difference in average mean blood pressure.…”
Section: Discussionmentioning
confidence: 99%